Impact of Corporate Governance on Research & Development Investment in The Pharmaceutical Industry in Indonesia - Rahmat Septiandendi; Adi Firman Ramadhan (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2021)
Deciding the investment scale of a company's Research & Development is a strategic investment decision related to creating long-term value of the company and it is a very important decision because it has a certain level of risk and the cost is not small. Corporate governance of a company differs according to the ownership structure of each company, and corporate governance will affect the company's decision-making. The purpose of this study is to examine the effect of corporate governance structure, namely major shareholder, institutional investor, and outside directors to investment research & development at a pharmaceutical company listed in Indonesian Stock Exchange period 2010 to 2017. The population of this study is a pharmaceutical company listed on the Indonesia Stock Exchange. The number of pharmaceutical companies listed during the period 2010 to 2017 is as many as 11 companies. By using purposive sampling, obtained a sample of 5 companies. The data analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that major shareholders have a positive significant influence on research & development investment. Meanwhile, the institutional investor has a positively significant influence on research & development investment. And the outside directors have an insignificant negative effect on investment & development investment.